Determination of interface toughness of functionally graded tungsten/EUROFER multilayer at 550 °C by analytical and experimental methods. (15th October 2018) - Qu, D.; Gaganidze, E.; Vaßen, R.; Aktaa, J.
Highlights: We evaluated interface toughness of functionally graded multilayer. We performed three and four-point bending tests on pre-cracked specimens at 550 °C. The energy release rate was assessed analytically and experimentally. Relationship between microstructure and energy release rate of interfacial crack propagation was reported. Abstract: As armor coating, functionally graded (FG) tungsten/EUROFER multilayer was sprayed on EUROFER substrate for First Wall application in fusion field. Interface toughness between FG tungsten/EUROFER multilayer and EUROFER substrate was studied innovatively by a simple method based on the beam theory in this paper. To quantify interface toughness, the energy release rate was assessed by performing three and four-point bending tests on pre-cracked specimens at 550 °C and under high vacuum. The energy release rate during propagating of interfacial crack was determined to be 258 J/m 2 and 225 J/m 2 analytically and experimentally for samples with 3 and 5 layers as FG-layer, respectively, which were calculated based on multi bending tests. Cross-section and fracture microstructure show a vast of plasticity in FG-layer, particularly in FG-layer with a higher volume ratio of EUROFER. Interfacial fracture microstructure indicates interface adhesion consists of mechanical interlocking and metallurgical bonding.